2019
DOI: 10.1016/j.jbiomech.2019.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Non-identifiability of parameters for a class of shear-thinning rheological models, with implications for haematological fluid dynamics

Abstract: Choosing a suitable model and determining its associated parameters from fitting to experimental data is fundamental for many problems in biomechanics. Models of shear-thinning complex fluids, dating from the work of Bird, Carreau, Cross and Yasuda, have been applied in highly-cited computational studies of heamodynamics for several decades. In this manuscript we revisit these models, first to highlight a degree of uncertainty in the naming conventions in the literature, but more importantly to address the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, when the characteristic shear rate is high, then the difference in the predicted shear viscosity values from the two sets of the best fitting parameters in the relevant shear rate range is rather small (within 10%); for this reason, they yield similar results in flow simulations, as demonstrated in Figure 11. Our results for the local shear rate, as shown in Figures 10b and 11b, were also obtained from two approaches, one from solving a nonlinear Equation (by combining Equations (10) and (11)) directly (shown as solid lines) and the other from numerical evaluations of the velocity gradient (see Equation (12)) from our numerical solutions of the velocity distribution. The latter results are shown as dashed lines in Figures 10b and 11b.…”
Section: Isothermal Flow In a Tubementioning
confidence: 58%
See 1 more Smart Citation
“…However, when the characteristic shear rate is high, then the difference in the predicted shear viscosity values from the two sets of the best fitting parameters in the relevant shear rate range is rather small (within 10%); for this reason, they yield similar results in flow simulations, as demonstrated in Figure 11. Our results for the local shear rate, as shown in Figures 10b and 11b, were also obtained from two approaches, one from solving a nonlinear Equation (by combining Equations (10) and (11)) directly (shown as solid lines) and the other from numerical evaluations of the velocity gradient (see Equation (12)) from our numerical solutions of the velocity distribution. The latter results are shown as dashed lines in Figures 10b and 11b.…”
Section: Isothermal Flow In a Tubementioning
confidence: 58%
“…As stated by Singh et al (2019) [9], people subjectively choose the fitting approach-thus, leading to nonunique inferences. Moreover, Gallagher et al (2019) [10] reported the non-identifiability in a family of shear-thinning rheological models. They found a class of parameter sets that fit the data evenly well.…”
Section: Introductionmentioning
confidence: 99%
“…Curve fitting of the common shear-thinning rheology models; Cross, Bird, Carreau and Yasuda relies on determination of parameters. Gallagher et al [57] found that the most common shear-thinning rheology models for blood had wide spectrum of uncertainty when fitting parameters to experimental data and an existing problem of parameter identifiability. This can ultimately affect the flow profiles, particularly important in complex flow fields such as those experienced in VADs and stenotic flows.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Four different temperatures (30ºC, 49ºC, 50ºC and 70ºC) and four concentrations (1%, 2%, 3% and 4%) were used to check their effect on the rheological properties of the mud. The Bingham model was used to explain the behavior of fluid which calculates the plastic viscosity and yield point as follows: [20].…”
Section: Rheological Propertiesmentioning
confidence: 99%